Ultrasound-responsive highly biocompatible nanodroplets loaded with doxorubicin for tumor imaging and treatment in vivo - Xiaoying Zhou; Lu Guo; Dandan Shi; Dong Meng; Xiao Sun; Mengmeng Shang; Xinxin Liu; Yading Zhao; Jie Li (Taylor & Francis Group, 2020)
As an injectable anticancer drug delivery system, the biological safety of nanocarriers is the most important prerequisite for their clinical application. The objective of our study was to synthesize special ultrasound-responsive highly biocompatible chitosan nanodroplets (BCNDs), observe their spatiotemporally control the delivery of doxorubicin (DOX) in vivo. The experimental results showed that the BCNDs were successfully prepared with high biosafety in vivo and great ultrasound imaging ability. DOX-BCNDs promoted the anticancer effects of DOX in vivo and inhibited the development of tumors. They also reduced the side effects to the heart and kidneys. In conclusion, BCNDs are a new type of smart nanocarrier with high biocompatibility and efficacy have great potential to be used in the clinic.